Mahomedian Church, San Fernando - (:unkn) unknown (My University, 2010)
Photo of mosque in San Fernando, Trinidad and Tobago.
Colour: Sepia; Style: Landscape; Other: Bordered, Undivided.
Keywords: Trinidad and Tobago; Postcards; Mosques--Trinidad and Tobago; Church buildings--Trinidad and Tobago; Islam--Trinidad and Tobago; Muslims--Trinidad and Tobago; Architecture--Trinidad and Tobago